Endoscopic forehead lift in combination with botulinum therapy and fillers: analysis of efficacy and safety - Pankovets, Nelli (ScienceRise: Medical Science, 2025)
The aim: Upper facial aging significantly impacts self-perception and quality of life as changes become apparent in the forehead, glabellar complex, and brow positioning. This narrative literature review evaluates clinical efficacy, safety profile and aesthetic outcomes of 3 treatment options: endoscopic forehead lift, botulinum toxin A and hyaluronic acid injectable dermal fillers, examining their individual and combined applications. Materials and methods: Literature was obtained between April and August 2025 from electronic databases: PubMed, ScienceDirect, Google Scholar, Nature, Wiley Online Library, ResearchGate, Springer and Clinical key; using targeted search strategies. Inclusion criteria encompassed articles discussing these interventions in human participants published between 2000-2025. Exclusion criteria included mid-/lower face procedures, animal studies and non-peer reviewed editorials. Forty-one sources were selected based on clinical relevance and methodological quality. Results: Endoscopic forehead lift demonstrated 93% patient satisfaction with superior long term structural repositioning. BoNT-A provided effective dynamic wrinkle reduction lasting 3-6 months with minimal complications. Hyaluronic acid fillers addressed volumetric deficits and static wrinkles lasting 6-18 months. Combined BoNT-A with HA fillers showed significantly enhanced outcomes, with 84.15% patient satisfaction at 6 months versus 55.12% with botulinum toxin A monotherapy. All modalities demonstrated excellent safety profiles with complications under 3%. Conclusions: Multimodal rejuvenation addressing multiple aging mechanisms simultaneously results in superior aesthetic outcomes and patient satisfaction compared to single modality procedures. Substantial evidence gaps exist regarding optimal sequencing and long-term outcomes of combined surgical-injectable approaches. Future prospective studies examining endoscopic procedures with injectable modalities across diverse populations are essential to establish evidence-based clinical protocols